PELATIHAN PEMBUATAN NOODLE FISH DARI IKAN RUCAH DI DESA MANGINDARA KECAMATAN GALESONG SELATAN KABUPATEN TAKALAR - Hardianty Askar; Istyqamah Muslimin; Arwita Irawati; Rasdi Rasdi; Muh Arfah Mustari (Nobel Community Services Journal, 2022)
This community service aims to provide socialization and training on the manufacture of fishery products by utilizing trash fish with low economic value into processed products of high quality and economic value through the application of technology by means of demonstration. The activity was carried out in Mangindara Village, South Galesong District, Takalar Regency. The product making activity involved 33 participants consisting of fishermen's wives, hamlet heads, and staff of the Magindara Village Office. There are several stages of the noodle fish making process, namely the fish is cleaned and then fillet and mashed. After that, combine the fish and other ingredients until evenly distributed, then knead until smooth and print using a noodle grinder until it is in the shape of noodles. Noodle fish is very popular with the people in Mangindara Village because it is quite easy and can enjoy the results of noodle fish production directly.